Kinerja Konselor pada Sekolah yang Tidak Memiliki Alokasi Jam Masuk Kelas - Prastiti, Efa Yuni (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this research is to know and analyze performance counselor at high schools 1 muntilan. The research is qualitative research with a case study. Research locations is high schools 1 muntilan. Technique data collection used is interview, observation, documentation. Technique data analysis use the model miles and huberman. Testing the validity of data using perseverance observation, member check, and triangulation. The research results show on the program planning bk is good , on the the implementation of the program bk be done in incidental so the implementation of less than optimal. The evaluation is good enough evidenced by evaluation report, and on the working mechanism is good administration a administration bk compiled very systematic and complete. So that it can be concluded that the state sma counselor at 1 muntilan less than maximum in implementation because they do not have hours class